Country Partnership Framework for the Republic of Indonesia for the Period FY16 - FY20 - World Bank Group (World Bank, Washington, DC, 2015)
Seventy years after independence and more than a decade of political and institutional reforms, Indonesia has emerged as a stable democracy. Indonesia’s achievements are now under stress, with a slowdown in its commodity driven economy, stagnant rates of poverty reduction, and rapidly rising inequality. The development policy review, completed in 2014, and the systematic country diagnostic (SCD), completed in 2015, explain the limited window of opportunity for Indonesia to reach high per capita income levels. This country partnership framework (CPF), covering the period FY2016-20, builds on the previous country partnership strategy (CPS) FY2013-15 and the long-term operational and policy-based support that has been a hallmark of World Bank Group’s (WBG’s) engagement with the Government of India (GoI) for the past decade. The CPF concentrates on areas of infrastructure necessary to better connect the economy, provide sustainable energy, help the country reap benefits from the rapid pace of urbanization, and improve equality of opportunity through better access of the poor and vulnerable to essential water and sanitation services. The CPF will seek to maximize synergies across the WBG and take advantage of all instruments in support of the CPF goals. The CPF will require a larger financing package than the previous CPS, although WBG’s total contribution will still be a very small percentage of overall borrowing needs.